Rohingya Muslims in Myanmar and their experience of long-term unending pains: aspects of human rights problem - Abdullah @ Chuah Hock Leng, Osman; Fatah Yasin, Raudlotul Firdaus; Muhamad Shukri, Abdul Salam; Zulkipli, Fakhrullah (IIUM Press, International Islamic University Malaysia, 2018)
Rohingya is an ethnic minority group that used to live in the Arakan belt of South East Burma bordering in the east with Thailand and in the North West with Bangladesh. Rohingya is the Muslim of Sunni followers and have been migrated from India for about a thousand years after the collapsed of Muslim empire from India. There are about 750,000 Muslims living in the Rakhine state and another one million living in the various parts of the world in United Kingdom, United States of America, Europe, Australia, Malaysia, Indonesia, etc. The location of the Rohingya concentration is of Arakan belt in South East Burma. This Rohingya is a minority group most persecuted violently and most unwanted people by the Burmese Buddhists in their country. According to some historical facts, Rohingyan is the native people of Rakhine state. Others said that they are immigrants from Bangladesh. There are some mentioned that when the Muslim India collapsed, they migrated to the Arakan belt (Simpson 2007: 267).